Relationship between Stress Levels and Blood Sugar Levels in Diabetes Mellitus - Irman, Veolina; Saridewi, Ratna Indah (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: The relationship between stress and blood sugar levels in individuals with diabetes mellitus is complex and can be influenced by various factors. When a person experiences stress, whether physical or emotional, the body responds by releasing stress hormones, can contribute to insulin resistance, a condition where the body's cells become less responsive to the effects of insulin. Furthermore, stress may affect a person's ability to manage diabetes effectively. Chronic stress, if not managed, can have long-term effects on the body, potentially contributing to the development of complications associated with diabetes. It's important to recognize that the relationship between stress and blood sugar levels varies among individuals Methods: We used descriptive analytic with cross sectional design. The population of this study were all patients with Diabetes Mellitus who were treated at the Internal Medicine Clcinic in Dr. Muhammad Zein general hospital Painan. The sample was taken as many as 79 respondents with accidental sampling technique. Data collection tool with documentation and questionnaire studies. Data analysis using chi square test. Results: The result showed that more than half of 49 respondents (62.0%) have an abnormal blood sugar levels, more than half of 54 respondents (68.4%) with moderate stress levels and there is a relationship between moderate stress levels and blood sugar levels with a value of α 0.000 (p value <0.05). Conclusion: The moderate stress levels are associated with increased blood sugar levels. The impacts of this study for nurses, that we must be able to review the psychosocial aspects of patients with diabetes mellitus and provide knowledge about diabetes mellitus either through direct counseling, dialogue, or through other information media such as posters, leafleats and social media.